3D METAL COMPLEXES WITH PHENOXYACETIC ACID DERIVATIVES: SYNTHESIS AND CRYSTAL STRUCTURES (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
Phenoxyacetic acid derivatives occupy an important place in coordination chemistry because they combine a chemically active carboxyl group with an aromatic aryloxy fragment that influences steric environment, electron density, supramolecular packing, and solid-state stability. In complexes of 3d-series metal ions, these ligands behave as structurally flexible O-donor systems and can coordinate in monodentate, chelating, or bridging modes. This determines whether the final products crystallize as hydrated mononuclear compounds, binuclear units, or extended coordination polymers. Published structural studies show that Co(II) and Ni(II) complexes of chlorophenoxyacetic acids often form octahedral environments with coordinated water molecules, whereas Cu(II) more readily gives square-planar or bridged motifs depending on synthesis conditions. Complexes based on 2,4-dichlorophenoxyacetic acid and 4-chlorophenoxyacetic acid demonstrate that the same ligand family can produce 0D, 1D, 2D, and 3D architectures, especially when auxiliary N-donor ligands or hydrothermal conditions are used. The scientific value of these compounds is not limited to structural chemistry. They are relevant for crystal engineering, modeling herbicide–metal interactions, studying the effect of coordination on biological and physicochemical behavior, and designing functional materials with tunable packing and intermolecular contacts.